Tocilizumab treatment in critical COVID-19: Report from a hospital center [Brief] - Hueda-Zavaleta, Miguel (2021)
A descriptive study was carried out, in which clinical and laboratory characteristics were evaluated in patients with a diagnosis of acute respiratory distress syndrome (ARDS) secondary to SARS-CoV-2 infection and who received Tocilizumab. Twenty four patients received Tocilizumab, the majority were male (95.8%), the most frequent comorbidity was obesity (33.3%). At the time of receiving Tocilizumab the median PAO2 / FiO2 was 159.5 (IQR 114.5-255, 3). Twenty-one (87.5%) patients presented clinical improvement and 3 (12.5%) died. Fifteen patients (62.5%) developed hepatotoxicity, the majority grade 3 (33.3%) and three (12.5%) patients presented grade 4 liver injury. Eleven patients (45.8%) presented bacterial superinfection, the more common organism being Acinetobacter baumannii. After the administration of Tocilizumab, more than half of the patients presented an adverse reaction; despite this, mortality was low, and the majority had a clinical improvement.